The macroeconomic impact of COVID‐19 in Mozambique: A social accounting matrix approach. (29th December 2021) - Betho, Rosario; Chelengo, Marcia; Jones, Sam; Keller, Michael; Mussagy, Ibraimo Hassane; van Seventer, Dirk; Tarp, Finn
Abstract: This study assesses the economic costs of COVID‐19 and the state of emergency implemented by the Government of Mozambique. We use a social accounting matrix multiplier analysis to estimate the effects of the pandemic on the economy. Our simulations suggest that the Mozambican economy lost 3.6 percentage points of GDP growth in 2020 and that employment was 1.9 percentage points down. These losses were primarily driven by export shocks, the most heavily affected sectors being trade and accommodation and mining. Mozambique faces a critical challenge of how to promote economic diversification and reduce vulnerability to foreign shocks.